2009
DOI: 10.1007/s10549-009-0483-1
|View full text |Cite
|
Sign up to set email alerts
|

Association between tumor tissue TIMP-1 levels and objective response to first-line chemotherapy in metastatic breast cancer

Abstract: In a previous study from our laboratory, high tumor levels of tissue inhibitor of metalloproteinases-1 (TIMP-1) have been associated with an adverse response to chemotherapy in metastatic breast cancer suggesting that TIMP-1, which is known to inhibit apoptosis, may be a new predictive marker in this disease. The purpose of this study was to investigate the association between TIMP-1 and objective response to chemotherapy in an independent patient population consisting of patients with metastatic breast cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 22 publications
1
9
0
Order By: Relevance
“…Although MMP expression generally has been associated with tumor progression in several cancer forms including breast cancer (36), clinical trials with broad-spectrum MMP inhibitors have failed, and in some cases, patients treated with the inhibitors even showed significantly poorer survival than patients receiving placebo (3). These results are further supported by recent data showing unfavorable effects of TIMP-1 in breast cancer patients (14)(15)(16). Moreover, recent data, including MMP-9 knockout mice, has clearly shown MMP-9 may be involved in tumor regression (5).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Although MMP expression generally has been associated with tumor progression in several cancer forms including breast cancer (36), clinical trials with broad-spectrum MMP inhibitors have failed, and in some cases, patients treated with the inhibitors even showed significantly poorer survival than patients receiving placebo (3). These results are further supported by recent data showing unfavorable effects of TIMP-1 in breast cancer patients (14)(15)(16). Moreover, recent data, including MMP-9 knockout mice, has clearly shown MMP-9 may be involved in tumor regression (5).…”
Section: Discussionsupporting
confidence: 76%
“…Similar to MMPs, the role of TIMPs in cancer is reported contradictory and both tumor-protective and tumor-enhancing properties have been reported (10)(11)(12)(13). In breast cancer patients, high tumor and serum levels of TIMP-1 have been associated with decreased response to chemotherapy and decreased survival, suggesting a detrimental effect of TIMP-1 (14)(15)(16).…”
mentioning
confidence: 99%
“…Among MMPs and TIMPs, TIMP-1 is frequently overexpressed and shown to serve as a prognostic marker in several types of human cancers including breast cancer, prostate cancer, lung cancer, melanoma, multiple myeloma, and glioblastoma [13], [14], [15], [16], [17], [18], [19], [20], [21]. This seemed at first counter-intuitive considering its prominent role in MMP inhibition, thereby suppressing matrix degradation necessary for tumor cell invasion.…”
Section: Introductionmentioning
confidence: 99%
“…In the exploratory study by Schrohl et al [36] results suggested that patients with high levels of TIMP-1 are less responsive to chemotherapy, but the study did not include an analysis of OS. On the other hand, the second study by Klintman et al [35] which supports the association of TIMP-1 with objective response to chemotherapy, did not find TIMP-1 to be associated with either progression free survival (PFS) or OS. The results presented in this manuscript suggest that TIMP-1 protein expression in cancer cells in the primary tumor evaluated by IHC is associated with improved OS for advanced breast cancer patients receiving D or GD.…”
Section: Discussionmentioning
confidence: 97%
“…The majority of breast cancer studies on TIMP-1 and association with prognosis and response to chemotherapy have focused on patients receiving adjuvant chemotherapy [2,8,18,20,34], whereas only two studies have included patients with advanced breast cancer [35,36]. These two studies both measured TIMP-1 levels in the primary tumors using an enzyme-linked immunosorbent assay-based approach and included patients receiving cyclophosphamide/methotrexate/5-fluorouracil or anthracycline-based chemotherapy.…”
Section: Discussionmentioning
confidence: 99%